N-methyl-D-aspartate improved social recognition potency in rats - Hlinák, Zdenek; Krejcí, Ivan (Neuroscience letters, 2002)
Activation of N-methyl-D-aspartate (NMDA) receptors is believed to play an important role in cognitive processes. In the present study we addressed the question of whether systematically administered NMDA can improve social recognition in adult male rats. We utilized the paradigm in which an adult animal is exposed to the same or a novel juvenile during two successive interactions. The adults given NMDA (10, 25 and 50 mg/kg, s.c.) immediately after the initial exposure to a juvenile exhibited significantly reduced social investigation during the second encounter with the same juvenile performed both 120 and 240 min later. Reduction in social investigation was not observed in saline treated animals as well as in those treated with both NMDA and saline but re-exposed to novel juveniles. These results indicate that NMDA improved social recognition potency of adult animals and prolonged retention of previously stored olfactory information.
Keywords: Animals; Memory, Short-Term; Behavior, Animal; N-methylaspartát; krátkodobá paměť; rozpoznávání (psychologie); sociální chování; Recognition, Psychology; Social Behavior; N-Methylaspartate; Male; chování zvířat; mužské pohlaví; krysa rodu Rattus; zvířata; Rats